2014
DOI: 10.1111/jasp.12231
|View full text |Cite
|
Sign up to set email alerts
|

Will to live in older people's medical decisions: immediate and delayed effects of aging stereotypes

Abstract: This research explores the duration of age stereotype priming effects on individuals' will to live when faced with a medical terminal illness decision. Study 1 established the content of the stereotype of the older age group in Portugal. Study 2 tested the effects of priming positive or negative age stereotypes on older and younger individuals' will to live, immediately after priming or after a delay. Results showed significant effects of stereotype valence on older people's will to live. As expected, immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 37 publications
3
36
0
1
Order By: Relevance
“…Structural equation modeling was also employed to examine whether an alternative sequence of the variables could fit the data and whether our conceptual model fully mediated the relationship between the implicit-intervention and the physical-function outcome. The p-values are presented as one-tail tests, because we hypothesized a direction of the effects based on prior single-session studies which found positive age-stereotype interventions improved outcomes (Cumming, 2012; Levy, 2009; Marques et al, 2014; Meisner, 2012). All analyses were conducted with SAS version 9.3 (SAS Institute Inc., Cary, NC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural equation modeling was also employed to examine whether an alternative sequence of the variables could fit the data and whether our conceptual model fully mediated the relationship between the implicit-intervention and the physical-function outcome. The p-values are presented as one-tail tests, because we hypothesized a direction of the effects based on prior single-session studies which found positive age-stereotype interventions improved outcomes (Cumming, 2012; Levy, 2009; Marques et al, 2014; Meisner, 2012). All analyses were conducted with SAS version 9.3 (SAS Institute Inc., Cary, NC).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, when individuals recognize through environmental cues that they have entered old-age, the age stereotypes that were applied to others acquire personal resonance, and thus become self-perceptions of aging, which can be activated by subsequent exposure to these cues; in turn, physical outcomes can then be impacted (Levy, 2009). Evidence supporting SET comes from single-session experiments that found age stereotypes influenced behavior only among, or were stronger among, older individuals for whom the stereotypes were self-relevant, in contrast to younger individuals for whom the stereotypes were self irrelevant (e.g., Levy, 2009; Marques, Lima, Abrams, & Swift, 2014; Meisner, 2012). In those studies, unlike the current one, self-perceptions of aging were not examined as part of the process.…”
mentioning
confidence: 99%
“…Hence, negative age stereotypes elicited a lower will to live only among older adults (Marques, Lima, Abrams, & Swift, 2014). The authors have attributed this to the fact that age stereotypes are highly relevant and more frequently used among older adults.…”
Section: Perceived Age Discrimination As a Precipitator Of Depressivementioning
confidence: 99%
“…The authors have attributed this to the fact that age stereotypes are highly relevant and more frequently used among older adults. Thus, the activation of these stereotypes occurs easily (Marques et al, 2014).…”
Section: Perceived Age Discrimination As a Precipitator Of Depressivementioning
confidence: 99%
“…Across many western cultures old age is perceived as a time of illness, frailty and dependency [16], [17]. Such prevalent negative age stereotypes can have a detrimental effect on the treatment older adults receive.…”
Section: Stereotypes Of Older Peoplementioning
confidence: 99%